2014
DOI: 10.1016/j.ejmp.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two treatment planning systems for volumetric modulated arc therapy optimization for prostate cancer

Abstract: For prostate cancer patients, VMAT treatment plans obtained with Monaco and Pinnacle offered clinically acceptable dose distributions. Further investigations are in progress to confirm the performances of the two TPS for irradiating more complex volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
0
10
0
3
Order By: Relevance
“…All plans were generated in Monaco v3.0.0 treatment planning system (TPS) (Elekta Corporation, Atlanta, GA) using Monte Carlo dose calculation algorithm with 6 MV photon beams. The treatment planning in Monaco is a two‐step process that calculates the optimal fluence in the first step and converts it into deliverable MLC segments in the later step (12‐14) . The treatment plan parameters, such as arc length, arc increment, arc start/stop angle, and minimum segment width, were handled based on tumor type and site.…”
Section: Methodsmentioning
confidence: 99%
“…All plans were generated in Monaco v3.0.0 treatment planning system (TPS) (Elekta Corporation, Atlanta, GA) using Monte Carlo dose calculation algorithm with 6 MV photon beams. The treatment planning in Monaco is a two‐step process that calculates the optimal fluence in the first step and converts it into deliverable MLC segments in the later step (12‐14) . The treatment plan parameters, such as arc length, arc increment, arc start/stop angle, and minimum segment width, were handled based on tumor type and site.…”
Section: Methodsmentioning
confidence: 99%
“…5 The Monte Carlo algorithm can improve dose calculation accuracy, which has been implemented successfully in clinical settings. Lafond et al 33 recently compared the Monaco TPS and Pinnacle™ TPS (Philips Medical Systems, Madison, WI) for VMAT plans, and found that the bladder wall, femoral heads and healthy tissue doses were significantly lower in Monaco plans. For PTV doses, Monaco plans had higher conformity than Pinnacle plans.…”
Section: Discussionmentioning
confidence: 99%
“…A wide distribution of low dose to the surrounding normal tissues can be harmful for the patients (18). The differences in DRs for the h-VMAT plan between the two treatment systems have not been compared in vivo 34: 331-337 (2020) In that study, the VMAT treatment plans obtained with Monaco and Pinnacle offered clinically acceptable dose distributions for prostate cancer (10). The DR of the RayStation plan compared to that of the Eclipse plan was wider and had a lower mean in our study.…”
Section: And Coronal (Lower) Dose Distribution Of >5 Gy For the Threementioning
confidence: 99%
“…Multiple commercial treatment planning systems (TPSs) have become available. Lafond et al, (10) have compared the dosimetric parameters of two VMAT treatment planning systems for prostate cancer, whereas Langner et al, (11) have compared point doses between Eclipse and Raystation (Eclipse Version 13.7.29; Varian Medical Systems, Palo Alto, CA, USA and RayStation version 4.7.4.4, RaySearch Medical Laboratories AB, Stockholm, Sweden) for proton therapy. The result of calculation is difficult between TPSs, because the calculation algorithm was different.…”
mentioning
confidence: 99%